2019
DOI: 10.1108/ebhrm-03-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Organisational embeddedness as a moderator on the organisational support, trust and workplace deviance relationships

Abstract: Purpose Emerging research calls for the exploration of the potential negative side of organisational embeddedness. It is important to assess such negative aspects to fully understand the power of embeddedness, and how to address the potential undesirable effects on employees and organisations. The purpose of this paper is to answer this call by assessing the extent to which organisational embeddedness can negatively influence the perceived organisational support-workplace deviance and the organisational trust–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 65 publications
6
15
0
1
Order By: Relevance
“…This finding is in line with studies by Darrat et al (2017); Siddique et al (2020) and Singh (2019a), which considered job embeddedness as a predictor, as well as with other studies by Jones (2015); Lawrence and Kacmar (2017); Marasi et al (2016) and Singh (2019b), which considered it as a moderator variable. By contrast, this finding is not consistent with those of Avey et al (2015); Collins and Mossholder (2017); Greene (2012); Holtom et al (2012) and Yusof et al (2019), who directly and indirectly confirmed the decreasing effect of job embeddedness on deviant behaviors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in line with studies by Darrat et al (2017); Siddique et al (2020) and Singh (2019a), which considered job embeddedness as a predictor, as well as with other studies by Jones (2015); Lawrence and Kacmar (2017); Marasi et al (2016) and Singh (2019b), which considered it as a moderator variable. By contrast, this finding is not consistent with those of Avey et al (2015); Collins and Mossholder (2017); Greene (2012); Holtom et al (2012) and Yusof et al (2019), who directly and indirectly confirmed the decreasing effect of job embeddedness on deviant behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…First, it considers job embeddedness as a potential context for cyberloafing. Second, considering how job satisfaction and internet addiction communicate with job embeddedness in a three-way interaction, this study further extends the previous empirical research (Avey et al, 2015;Collins and Mossholder, 2017;Darrat et al, 2017;Greene, 2012;Jones, 2015;Marasi et al, 2016;Siddique et al, 2020;Singh, 2019aSingh, , 2019bYusof et al, 2019), which investigated the job embeddedness-deviant behaviors relationship in the form of a two-way interaction model. Third, bringing together the organizational adversity/ prosperity, level of embeddedness and typical positive and negative intervening factors, this study practically provides the human resource managers with critical insights about decreasing cyberloafing among employees.…”
Section: Cyberloafing In Public Sectorsupporting
confidence: 66%
See 2 more Smart Citations
“…Al respecto, el apoyo organizacional tiene un efecto positivo en el desempeño de los colaboradores, la innovación (Suifan et al, 2018;Chen et al, 2020) y la capacidad de respuesta a los cambios del entorno (Ferreira et al, 2018). Además, el apoyo organizacional percibido aumenta la creatividad y el sentido de pertenencia (Suifan et al, 2018;Tang et al, 2017), al tiempo que mejora el ambiente de trabajo, el compromiso (Arasanmi y Krishna, 2019) y la integración organizacional (Singh, 2019). De acuerdo con los planteamientos anteriores, la Tabla 1 presenta los aspectos observados respecto a las condiciones de aprendizaje organizacional.…”
Section: Soporte Organizacionalunclassified